Effect of cooling methods on dimensional accuracy and surface finish of a turned titanium part - Islam, Mohammad Nazrul; Anggono, J.; Pramanik, Alokesh; Boswell, Brian (Springer, 2013)
In metal cutting, the choice of cooling method influences the deformation mechanism, which is related to the dimensional accuracy and surface finish of the parts. The deformation mechanism of titanium alloys under machining conditions is known to be very different from that of commonly used industrial materials. Therefore, the effect of cooling methods on dimensional accuracy and surface finish in machining titanium is of particular interest. This paper investigates experimentally and analytically the influence of cooling method and cutting parameters on two major dimensional accuracy characteristics of a turned titanium part—diameter error and circularity, and surface finish. Data were analyzed via three methods: traditional analysis, Pareto ANOVA, and Taguchi method. The findings indicate that the cooling method has significant effect on circularity error (contribution ratio 76.75 %), moderate effect on diameter error (contribution ratio 25.00 %), and negligible effect on surface finish (contribution ratio 0.16 %).